Burden, demographic patterns, and temporal trends of parotitis in Saudi Arabia, 2015–2023: a multicenter electronic health record study - Saleem, Rimah Abdullah; Sukkarieh, Hatouf; Alkattan, Rana K.; Bustami, Rami; Daher, Sarah; Alhusseini, Noara; Fakhoury, Rajaa (Frontiers in Epidemiology, 2026)
BackgroundParotitis is an inflammation of the parotid glands. It can be acute or chronic based on etiological factors such as bacterial and viral infections, autoimmune and metabolic disorders. The prevalence and characteristics of parotitis among the Saudi population are unknown. Therefore, this study aimed to explore the frequency, demographic patterns, and temporal trends of parotitis in Saudi Arabia.MethodologyThis was a multicenter, retrospective cohort study using electronic health record data from five tertiary medical centers (Riyadh, Jeddah, Dammam, Madinah, and Taif) of the Ministry of National Guard Health Affairs (NGHA) between 2015 and 2023. Data from clinically diagnosed patients with parotitis were collected, including demographics, patient type, body mass index (BMI), and region. Statistical analysis was conducted using R (version 4.3.2). Categorical variables were expressed as counts (%) and continuous variables as mean (SD) or median (IQR), as appropriate. Several statistical tests were performed, including annual counts and proportions for temporal trends, and join-point regression to estimate data-driven change points. Statistical significance was estimated at a P-value of less than 0.05.ResultsA total of 1,340 cases of parotitis were recorded between March 2015 and March 2023. The average age at diagnosis was 27.2 years. Males accounted for 54.6% of this cohort, 36.67% of the patients were underweight, and 19.2% were obese. Additionally, 49% of the cases were inpatients, and the majority (66.1%) resided in Riyadh. Within the designated timeframe (2015–2023), no significant changes in parotitis occurrence were observed, especially during the COVID-19 pandemic, with a higher frequency among patients aged 1–20 years.ConclusionThis exploratory study characterized parotitis cases among Saudi patients. The high frequency of parotitis diagnosis among children and adolescents compared to adults, along with other demographic characteristics, highlights the need to understand the underlying factors that could improve clinical awareness, documentation, and prevention strategies.